Multinationals, Institutions and the Construction of Transnational Practices 2006
DOI: 10.1057/9780230502307_5
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Motivations for Global HRM Integration

Abstract: For many years, the field of international human resource management (IHRM) has struggled with the question of whether or not it is better for a multinational firm (MNC) to integrate its IHRM function across the various geographies in which it operates. By integration, I refer to the quest for consistency of HR philosophy, policies and practices across the MNC's operations worldwide. Looked at from one angle, the debate is rather a bizarre one. Does it really make any sense for a MNC to undertake 2 integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Future research should consider exogenous variables such as institutional distance, environmental complexity, and dynamism. Scholars have long established that MNEs cannot simply adopt HRM practices that fit the firm's strategy, but MNEs must also consider local environmental requirements (Lazarova et al, 2016;Taylor et al, 2006). We assume that strategies are path dependent and hard to change.…”
Section: Gte Management and Performance In Mnes 33mentioning
confidence: 99%
“…Future research should consider exogenous variables such as institutional distance, environmental complexity, and dynamism. Scholars have long established that MNEs cannot simply adopt HRM practices that fit the firm's strategy, but MNEs must also consider local environmental requirements (Lazarova et al, 2016;Taylor et al, 2006). We assume that strategies are path dependent and hard to change.…”
Section: Gte Management and Performance In Mnes 33mentioning
confidence: 99%
“…In this regard, corporate integration is defined as "centralized control over key resources and operations that are strategic in the value chain" (Evans et al, 2002: 103). Two factors contribute to the increasing desire to integrate HRM policies in MNEs -the growing focus on creating social capital throughout the MNE's global internal network, and the increasing emphasis on ensuring the sustainability of MNE's global operations (Taylor, 2006). Global integration, in turn, facilitates the development of a common corporate culture and has the potential to enhance equity and procedural justice within the MNE through the transfer of organizational practices (Rosenzweig and Nohria, 1994).…”
Section: Global Mobility As Organization Development Co-ordination Amentioning
confidence: 99%
“…Second, we found the usage of a global HR policy formation committee to positively influence engagement in GTM. Although only a sparse literature discusses HR policy formation bodies, there is evidence to indicate greater utilization of such bodies (Taylor, 2006;Tregaskis, Glover & Ferner, 2005). It has been suggested that the presence of such global bodies may indicate a view within the MNE about the value managers from different country operations can bring to the table (Marginson et al, 1995).…”
Section: One Of Our Major Concerns Is the Lack Of Succession Planningmentioning
confidence: 99%